Pemanfaatan/Pengolahan Pisang Menjadi Makanan Ringan Berupa Keripik Pisang Dan Cemilan Di Desa Kecupak Ii Kab. Pakpak Bharat (Ulangan 28:8) - Nino Sampe Tindih Sitohang; Ibelala Gea (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This journal discusses the utilization/processing of bananas into snacks such as banana chips and snacks in Kecupak II Village, Pakpak Bharat Regency. Bananas are not prominently featured in that area, but they have been optimized into a marketable product, namely banana chips. Therefore, this research aims to optimize the utilization and processing of bananas into value-added products. The principle in Deuteronomy 28:8 provides a foundation for blessings in conducting a business. Processed banana products have good market potential in Kecupak II Village and its surroundings. Besides serving as a healthy snack alternative, these products can also be an additional source of income for the local community. The utilization and processing of bananas into snacks in Kecupak II Village hold promising potential. It is hoped that this research can make a positive contribution to the development of banana agro-industry in this region.